Usability Assessment of Moodle by Brazilian and Portuguese Nursing Students. Issue 6 (June 2016) - Seixas, Carlos Alberto; de Godoy, Simone; Martins, JoséÉ Carlos Amado; Mazzo, Alessandra; Baptista, Rui Carlos Negrão; Mendes, Isabel Amélia Costa
Abstract : Distance education has turned into an important tool for nursing education. The virtual learning environments contribute toward an interactive and attractive educational process. In this study, we assess the usability of a virtual learning environment that was developed to teach nursing students how to care for patients with urinary retention. A multicenter and descriptive study was undertaken, which involved nursing students from the University of São Paulo at Ribeirão Preto College of Nursing, Brazil, and the Escola Superior de Enfermagem de Coimbra, Portugal. The participants were 79 students, mostly female, between 20 and 24 years of age. The virtual learning environment revealed good properties in terms of usability on most criteria. Future research will help to confirm the results.